Left Atrial Appendage Ligation in Patients With Atrial Fibrillation Leads to a Decrease in Atrial Dispersion - Kawamura, Mitsuharu (J Am Heart Assoc, 2015)
BACKGROUND: Left atrial appendage (LAA) exclusion has been performed in patients with atrial fibrillation (AF) to prevent thrombus formation and subsequent cardioembolic events. Left atrial electrical remodeling is a recognized factor in the recurrence of AF. The effects of LAA exclusion on P-wave characteristics and left atrial electrical remodeling have not been well described. The purpose of this study was to evaluate the effect of LAA ligation on P-wave morphology in patients with AF. METHODS AND RESULTS: Fifteen patients who were in sinus rhythm during the LAA ligation procedure were included in the study. We evaluated the P-wave characteristics, including P-wave duration, P-wave amplitude, PQ interval, and P-wave dispersion, before and after ligation. Eleven patients had paroxysmal AF and 4 patients had persistent AF (12 male patients and 3 female patients). P-wave duration immediately after ligation was significantly shorter compared with baseline in all limb leads except lead aVR (P<0.05). P-wave amplitude immediately after ligation was significantly greater compared with baseline in inferior leads; however, P-wave amplitude after 1 to 3 months was significantly lower compared with immediately after ligation. PQ interval immediately after ligation was significantly shorter compared with baseline (P=0.01), and P-wave dispersion after 1 to 3 months was significantly shorter compared with baseline (P=0.02). CONCLUSIONS: LAA exclusion produces consistent P-wave changes consistent with decreased atrial mass and decreased atrial dispersion that may represent reverse electrical atrial remodeling. This is a potential mechanism to explain the role of LAA ligation in maintaining sinus rhythm in patients with AF.